2019
DOI: 10.3389/fmicb.2019.02793
|View full text |Cite
|
Sign up to set email alerts
|

Deep Microbial Colonization in Saponite-Bearing Fractures in Aged Basaltic Crust: Implications for Subsurface Life on Mars

Abstract: One of the most promising planetary bodies that might harbor extraterrestrial life is Mars, given the presence of liquid water in the deep subsurface. The upper crust of Mars is mainly composed of >3.7-billion-year-old basaltic lava where heat-driven fluid circulation is negligible. The analogous crustal environment to the Martian subsurface is found in the Earth's oceanic crust composed of basaltic lava. The basaltic crust tends to cool down for 10–20-million-years after formation. However, microbial life in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Analytical procedures have been developed to visualize and quantify microbial cells hosted in crack-infilling minerals in the oceanic crust by preparing thin sections of rocks embedded in hydrophilic resin called LR White 8,9 . Microbial cells embedded in the resin are stainable with a DNA dye called SYBR-Green I.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical procedures have been developed to visualize and quantify microbial cells hosted in crack-infilling minerals in the oceanic crust by preparing thin sections of rocks embedded in hydrophilic resin called LR White 8,9 . Microbial cells embedded in the resin are stainable with a DNA dye called SYBR-Green I.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of saponite is based on studies that show Fe-rich saponite were able to promote and preserve precursors of biopolymers and this may have contributed to prebiotic chemistry on Earth and the deep biosphere [17]. Sueoka et al studied the mineral-filled fractures of a basaltic rock core sample obtained during the Integral Ocean Drilling Project Expedition 329 and found that these minerals were rich in Mg-rich saponite and calcium carbonate [23]. The saponite-rich clay fraction in the core contains a much higher organic carbon than the bulk counterpart suggesting enough supply of energy and carbon sources for a saponite-hosted life [23].…”
Section: Introductionmentioning
confidence: 99%
“…Sueoka et al studied the mineral-filled fractures of a basaltic rock core sample obtained during the Integral Ocean Drilling Project Expedition 329 and found that these minerals were rich in Mg-rich saponite and calcium carbonate [23]. The saponite-rich clay fraction in the core contains a much higher organic carbon than the bulk counterpart suggesting enough supply of energy and carbon sources for a saponite-hosted life [23]. Apart from the possible contributions of saponites to early life, another reason for the interest in the system is the observation that saponites are easy to synthesize and their structures can be functionalized and modulated to obtain a wide variety of interesting novel advanced layered materials for use in heterogeneous catalysis [17] or for protection of organic compounds from photolysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of saponite is based on studies that show Fe-rich saponite were able to promote and preserve precursors of biopolymers and this may have contributed to prebiotic chemistry on Earth and the deep biosphere [17]. Sueoka et al studied the mineral-filled fractures of a basaltic rock core sample obtained during Integral Ocean Drilling Project Expedition 329 and found that these minerals were rich in Mg-rich saponite and calcium carbonate [23]. The saponite-rich clay fraction in the core contains a much higher organic carbon than the bulk counterpart suggesting enough supply of energy and carbon sources for a saponite-hosted life [23].…”
Section: Introductionmentioning
confidence: 99%
“…Sueoka et al studied the mineral-filled fractures of a basaltic rock core sample obtained during Integral Ocean Drilling Project Expedition 329 and found that these minerals were rich in Mg-rich saponite and calcium carbonate [23]. The saponite-rich clay fraction in the core contains a much higher organic carbon than the bulk counterpart suggesting enough supply of energy and carbon sources for a saponite-hosted life [23]. Apart from the possible contributions of saponites to early life, another reason for the interest in the system is the observation that saponites are easy to synthesize and their structures can be functionalized and modulated to obtain a wide variety of interesting novel advanced layered materials for use in heterogeneous catalysis [17] or for protection of organic compounds from photolysis [24].…”
Section: Introductionmentioning
confidence: 99%